Characterizing the bacterial communities associated with Mediterranean sponges: a metataxonomic analysis - Esposito, Roberta; Federico, Serena; Sonnessa, Michele; Reddel, Sofia; Bertolino, Marco; Ruocco, Nadia; Zagami, Giacomo; Giovine, Marco; Pozzolini, Marina; Guida, Marco; Zupo, Valerio; Costantini, Maria (Frontiers in Microbiology, 2024)
The oceans cover over 70% of our planet, hosting a biodiversity of tremendous wealth. Sponges are one of the major ecosystem engineers on the seafloor, providing habitat for a wide variety of species to be considered a good source of bioactive compounds. In this study, a metataxonomic approach was used to describe the bacterial communities of the sponges collected in Faro Lake (Sicily) and in Porto Paone (Gulf of Naples). Four sponges were identified by morphological analysis and amplification of the conserved molecular markers 18S and 28S (RNA ribosomal genes), CO1 (mitochondrial cytochrome oxidase subunit 1) and ITS (internal transcribed spacer). Metataxonomic analysis of sponges revealed a large number of Amplicon Sequence Variants (ASVs) belonging to the phyla Proteobacteria, Cloroflexi, Dadabacteria and Poribacteria. In particular, Myxilla (Myxilla) rosacea and Clathria (Clathria) toxivaria displayed several classes such as Alphaproteobacteria, Dehalococcoidia, This is a provisional file, not the final typeset article Gammaproteobacteria, Cyanobacteria and Bacteroidia. On the other hand, the sponges Ircinia oros and Cacospongia mollior hosted bacteria belonging to the classes Dadabacteriia, Anaerolineae, Acidimicrobiia, Nitrospiria and Poribacteria. Moreover, for the first time, in the sponge M. (Myxilla) rosacea was revealed the presence of Rhizobiaceae bacteria which found mainly associated with soil and plants and involved in biological nitrogen fixation.